Development and Synchrotron‐Based Characterization of Al and Cr Nanostructures as Potential Calibration Samples for 3D Analytical Techniques. Issue 6 (7th December 2017) - Dialameh, Masoud; Ferrarese Lupi, Federico; Hönicke, Philipp; Kayser, Yves; Beckhoff, Burkhard; Weimann, Thomas; Fleischmann, Claudia; Vandervorst, Wilfried; Dubček, Pavo; Pivac, Branko; Perego, Michele; Seguini, Gabriele; et al.
Abstract : The continuous and aggressive scaling in semiconductor technology results in the integration of increasingly complex 3D architectures and new materials. The realization of these downscaled 3D structures requires also further improvement in 3D characterization techniques. In this work, a potential route to improve the accuracy and reliability of the quantitative analysis of 3D nano‐devices is investigated. 3D organic and inorganic reference nanostructures with dimensions and structural ordering resembling those utilized in industrial applications are fabricated and characterized in detail. The 3D organic nanostructures are fabricated exploiting the self‐assembly capability of di‐block copolymers. Subsequent deposition of a thin Al film lead to the formation and realization of nanostructured Al. In addition, different inorganic nanostructures are fabricated using electron beam lithography. The various nanostructures are characterized with respect to their dimensions as well as composition using various analytical techniques namely reference‐free grazing incidence X‐ray fluorescence, grazing incidence small angle X‐ray scattering, scanning electron microscopy, and spectroscopic ellipsometry. Abstract : 3D‐chemical analysis is becoming a crucial step in the development of increasingly complex devices based on 3D architectures and new materials, as well as quality control during the manufacturing process. Therefore, there is an urgent need for metrology to provide 3D inorganic and organic/inorganic reference samples at sub‐micrometer scale to assess the reliability of such chemical analysis.